The Effect of Sidaguri Leaf Infusa (Sida rhombifolia L) On Uric acid levels in mice Male (Mus musculus) - Megawati Megawati; Fadila Nur (Jurnal Farmasi Sandi Karsa, 2021)
Research has been conducted on the effect of Sidaguri (Sida rhombifolia L.) Leaf Infusion on Uric Acid Levels in Male Mice (Mus musculus) with the aim of researching the effect of Sidaguri (Sida rhombifolia L.) Leaf Infusion on reducing blood uric acid levels in white male mice that were treated with induced by caffeine. This study is an experimental study, by testing the decrease in uric acid levels using Allopurinol and Sidaguri Leaf Infusion (Sida Rhombifolia L.) with concentrations of 5g/BW, 10g/BW, 20g/BW in Male Mice (Mus Musculus) induced with 13 mg Caffeine. The results showed that Sidaguri Leaf Infusion (Sida rhombifolia L.) could reduce uric acid levels in the blood of male mice (Mus musculus) induced with caffeine, but the difference in doses of Sidaguri Leaf Infusion (Sida Rhombifolia L.) was not significantly affected.